2007
DOI: 10.1002/jbm.b.30894
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility testing of simulated total joint arthoplasty articulation debris

Abstract: Surface characterization was performed to evaluate the surface condition of an uncoated cobalt alloy disc (control), and discs with medium and thick boron coatings for total joint articulating surfaces. Discs were characterized by scanning electron microscopy before and after dissolution studies. Chemical analyses of elemental transfer to the solution were assessed to evaluate the surface stability of the new coating. An in vivo biocompatibility study for particulates [of boron (B), titanium alloy (Ti), cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Moreover, ion release from boron, when it occurs, is expected to be in the form of boric acid, which is a mild antiseptic, commonly used in ophthalmic solutions. The results of a recent, standardized biocompatibility study of boron, and boron-coated Co-Cr-Mo are consistent with these expectations, and will be reported separately from this paper [16].…”
Section: Introductionsupporting
confidence: 83%
“…Moreover, ion release from boron, when it occurs, is expected to be in the form of boric acid, which is a mild antiseptic, commonly used in ophthalmic solutions. The results of a recent, standardized biocompatibility study of boron, and boron-coated Co-Cr-Mo are consistent with these expectations, and will be reported separately from this paper [16].…”
Section: Introductionsupporting
confidence: 83%
“…In contrast to various in vitro cell culture studies that focus on one cell type [32,40], the murine model can not only reflect complex cellular and tissue interactions, but can also mimic the dynamic process of joints. Additionally, compared with other models, such as hamsters' skinfold-chamber models [41] and "air pouch" models [42], results from this model, as the suspensions were injected intraarticularly, are easier to translate into a clinical scenario because the generated wear debris primarily accumulates in the joint that has been replaced. In terms of the characteristics of metal materials, the CoCrMo particles and ions used in our study were consistent with those found in some clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…A common accepted theory of metal wear debris is that it is capable of stimulating the formation of aseptic lymphocytic vasculitis lesions around the prosthesis, which is characterized by diffusing lymphocytic infiltrates and extensive connective tissue necrosis [46]. Various other animal models that have attempted to study aseptic implant loosening, such as hamsters' skinfold-chamber models [46] and “air pouch” models [47], have yielded to date unreliable and limiting information that is not translatable into the clinical scenario, as the particle stimulation site does not correlate with the situation after surgery: the generated wear debris primarily accumulates in the joint that had been replaced. Different from other studies, this study uses an animal model to compare the biological inflammatory response of CoCr particles and CoCr ions in the knee joint in vivo .…”
Section: Discussionmentioning
confidence: 99%